Pola Pengobatan Covid-19 pada Pasien Komorbid di RSUD dr. La Palaloi: The Pattern of Treatment for Covid19 in Comorbid Patients at the dr. La Palaloi Hospital - Dwi Fitrah Wahyuni; An Nisaa Nurzak; Arifuddin Yunus; Nabilah Baharuddin; Sitti Nur Intang (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
As stated by the World Health Organization (WHO) as a global pandemic on March 11, 2020, Coronavirus Disease 2019 (Covid-19), a disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), [1]. For suspected and confirmed Covid-19 patients with mild symptoms, the use of antibiotic drugs is not recommended, both for therapy and prevention [2] .After WHO declared Covid-19 a global pandemic, RSUD dr. La Palaloi is one of the hospitals appointed by the government as a referral hospital for handling Covid-19 in Maros district, South Sulawesi. Comorbidity is one of the factors that causes the mortality rate in patients infected with Covid-19 to increase. The purpose of this study was to describe the pattern of prescribing Covid-19 drugs for comorbid patients. The research method used is a retrospective research method to determine the pattern of Covid-19 treatment with comorbid patients at dr. La Palaloi. The most common comorbidity is hypertension. The most antibiotics given to Covid-19 patients were Azithromycin and the most Antibiotics were Oseltamivir. Treatment for the first Covid-19 patient was given antibiotics and antivirals. Treatment for antihypertensives is the CCB group, for the treatment of diabetes is insulin, and for the treatment of bronchopneumonia, antibiotics are given.